Internal control as a tax governance mechanism for mitigating transfer pricing risks - Hanin Febriana; Lidya Primta Surbakti (PT WIM Solusi Prima, 2026)
This study aims to examine the role of internal control as a tax governance mechanism in mitigating transfer pricing risks in multinational enterprises. Transfer pricing remains a critical issue in international taxation due to its potential to generate tax adjustments, tax disputes, and compliance uncertainties when not properly managed. This study employs a literature review approach by analyzing scholarly articles obtained from various academic databases. The analysis was conducted through a systematic process of identification, screening, and synthesis of literature related to internal control, tax governance, and transfer pricing risk. The findings indicate that internal control plays a strategic role in supporting tax governance through enhanced monitoring mechanisms, tax risk management, and transfer pricing compliance. The implementation of a Tax Control Framework, adequate transfer pricing documentation, and cooperative compliance practices contribute to controlling tax risks and reducing the likelihood of tax adjustments and transfer pricing disputes. The study also reveals that transfer pricing risk is influenced not only by technical pricing considerations but also by the effectiveness of tax governance and the quality of a firm's internal control system. Therefore, the integration of internal control and tax governance is essential for strengthening transfer pricing compliance and mitigating tax risks in multinational enterprises.